Dynasties and Democracy in Japan - Łagnowska, Sylwia (New Dynamics in Asia, 2020)
One of the rules of democracy is that everyone can be a politician, but even in a democratic system there is a phenomenon called “democratic dynasties.” Democratic dynasties mean that multiple members of one family become politicians. In a democracy with long democratic traditions, normally 5%–10% of all legislators come from democracy dynasties and this phenomenon declines over time. Except Japan. After the Second World War, about 3% of the members of Japan’s Parliament were related to previous members of the pre-war government. Since then, the proportion of legacy MPs in the Parliament subsequently increased toward over 40% by the late 1980s. Moreover, in the Liberal Democratic Party (LDP), which has been the dominant party in Japan since 1955, nearly half of all members in the 1980s and early 1990s were legacies. Currently, the proportion is decreasing, but is still more than 25%. The author analyzes the democratic dynasties phenomenon in Japan, trying to understand why in Japan, unlike other countries, the proportion of legacies is so high.